Optimization of 3D Printing Parameter Process for Product Tensile Strength from PLA Materials Using the Taguchi Method - I Made Londen Batan; Arleta Listiyana Chandradewi; Arif Wahjudi; Dinny Harnany (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2023)
Three-dimensional printing or 3D Printing is one of the revolutionary machines in addictive manufacturing techniques to create three-dimensional objects with complex structures. Until now there are many techniques in 3D printing, one of which is Fused Deposition Modeling (FDM), which is currently widely used because of its ease and low operational costs. However, in the printing process, there are important things that must receive attention, namely the process parameters. Because this is what really determines the quality of the printout. In this research, an analysis of the effect of process parameters such as: infill rate, infill pattern, extrusion temperature and layer thickness were carried out on the tensile strength of the printed product. The method used is the Taguchi method with the Orthogonal Array L 9 (3 4) experimental design. Three tensile test specimens were printed for each variation using a Cubic Chiron 3D printer, so a total of 27 specimens were printed. All specimens were tensile tested according to ASTM D638 standard, the results were analysed based on the average value and signal to ratio (SNR) value and their significance by analysis of variance (ANOVA). The results of the analysis show that the infill rate, infill pattern and layer thickness have a significant effect on the tensile strength of the printing results. The optimal value of the tensile strength is 56,876 MPa, occurs in the concentric pattern with an infill rate of 90%, and a layer thickness of 0.2 mm. From the confirmation test, the confidence interval values were obtained from 55,477 MPa to 58,275 MPa, meaning that the optimal predictive value was not significantly different from the confirmation test value.